2013
DOI: 10.1016/j.neuron.2012.11.032
|View full text |Cite
|
Sign up to set email alerts
|

Feedback Inhibition Enables Theta-Nested Gamma Oscillations and Grid Firing Fields

Abstract: Cortical circuits are thought to multiplex firing rate codes with temporal codes that rely on oscillatory network activity, but the circuit mechanisms that combine these coding schemes are unclear. We establish with optogenetic activation of layer II of the medial entorhinal cortex that theta frequency drive to this circuit is sufficient to generate nested gamma frequency oscillations in synaptic activity. These nested gamma oscillations closely resemble activity during spatial exploration, are generated by lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
376
6
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 269 publications
(425 citation statements)
references
References 51 publications
37
376
6
1
Order By: Relevance
“…When the hippocampus is inactivated, the hexagonal firing pattern of the grid cells is lost and the cells become responsive instead to other influences such as head direction signals 109 . The elimination of grid structure correlates strongly with the induced drop in firing rates of the grid cells and is consistent with the need for external excitatory input proposed by inhibitory network models of grid cells 101,107,108 . The dependence on external excitation, from the hippocampus or elsewhere, does not rule out a role for hippocampal backprojections in other functions of grid cells, such as in updating position coordinates based on environment-specific maps stored in the hippocampus.…”
Section: Grid Cells and The Formation Of Place Fieldssupporting
confidence: 84%
See 2 more Smart Citations
“…When the hippocampus is inactivated, the hexagonal firing pattern of the grid cells is lost and the cells become responsive instead to other influences such as head direction signals 109 . The elimination of grid structure correlates strongly with the induced drop in firing rates of the grid cells and is consistent with the need for external excitatory input proposed by inhibitory network models of grid cells 101,107,108 . The dependence on external excitation, from the hippocampus or elsewhere, does not rule out a role for hippocampal backprojections in other functions of grid cells, such as in updating position coordinates based on environment-specific maps stored in the hippocampus.…”
Section: Grid Cells and The Formation Of Place Fieldssupporting
confidence: 84%
“…The prime challenge is the almost complete lack of excitatory connections between layer II stellate cells, the cell type containing the largest number of grid cells and the most regular grid patterns 9,26,[103][104][105] . Paired recordings have shown that excitatory connections are nearly absent among stellate cells in adult animals and that stellate cells are instead strongly connected via fast-spiking inhibitory interneurons [106][107][108] . The inhibition between pairs of stellate cells seems to be consistent in magnitude, i.e.…”
Section: Attractor Network and Mechanisms Of The Grid Patternmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, computational studies have identified canonical circuit motifs of theta-gamma correlation in which the theta phase can be instrumental in triggering and even generating gammaband activities in postsynaptic target circuits (17,40). Key assumptions of such "theta-reset models" are the existence of a robust gamma-generating feedback circuit in the target structure, and a low-frequency (theta periodic)-modulated input to inhibitory cells in the circuit (17,41,42). This low-frequency (theta)-modulated input may likewise be generated de novo from within the circuit from theta-generating or theta-resonating interneuron populations (figure 1A in ref.…”
Section: Discussionmentioning
confidence: 99%
“…We thus correlated burst-LFP synchronization of neurons recorded at LFP recording sites that provided theta-phase or gamma-amplitude variations for theta-gamma correlations (SI Result S13). We found that burst synchronization to remote LFP gamma activity varied proportionally with the degree of theta-phase correlation with low-gamma amplitudes (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50), an effect that was limited to those LFP sites that showed significant theta-gamma correlations (Spearman rank correlation r = 0.2, P = 0.044; Table S2 and SI Result S13). To our knowledge, these findings provide the first quantitative evidence that recording sites with LFP theta phases that engage in longrange gamma correlations also host neurons whose burst firing events synchronize long-range to gamma activity.…”
Section: Theta-gamma Correlation and Its Relation To Synchronization Ofmentioning
confidence: 95%